The importance of social capital in agriculture - Bencze Tibor (University of Szeged, Faculty of Agriculture Szeged, 2019)
The concept of social capital became known in the 1980’s as an immaterial resource in the society and it is also a popular area of sociological and economic researches nowadays. Bourdieu, Coleman, and Putnam created the fundamental conceptions of the social capital. Defining social capital as capital involves the philosophy of serving as a resource for the social network. Studies of the rapidly growing economy of East Asia always emphasize the importance of dense social networks. These networks, the unacceptable, the confidential, reduce the transaction costs, speed up the flow of information and innovation. Social capital and financial capital can be converted. The great economic developments in Hungarians in the last century are different from these causes. In Hungary, there is a very low level of cooperation as well as willingness to develop it. Among Western European countries the level of trust is lower than the average. This basic problem is closely related to the low level of trust and social capital in society as a whole. Partnerships and cooperations are essential nowadays as they can be beneficial to the whole society and economy. In addition, the farmers' eagerness to associate is also weak and the options on how to resolve this issue are still not settled. Enforcement of the Hungarian peasantry in agricultural cooperatives (1958-1962) left a profound impression on society and its consequences must be taken into account. The good reputation and the credit could be quickly lost; on the contrary recovery – especially rebuild mutual trust- takes more time. Hungarian farmers do not have the confidence to regain each other in the long run. It should be changed, otherwise the majority of the Hungarian farmers will not have the chance to stay competitive.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok